KNOWLEDGE FOR TEACHING MATHEMATICS TO STUDENTS WITH SPECIAL EDUCATION NEEDS WITH LEARNING DISABILITIES: A NEED ANALYSIS (Proceedings of International Conference on Special Education, 2025)
Teaching mathematics to students with special educational needs (SEN) demands specialized pedagogical competencies beyond general teaching skills. However, previous studies indicate that many special education teachers lack sufficient training specifically in mathematics pedagogy, hindering their ability to address the learning challenges of SEN students. This study addresses the identified gap in understanding teachers' perceptions regarding the specific pedagogical knowledge necessary for effective mathematics instruction for SEN students, alongside evaluating teachers’ actual knowledge and experience levels in this domain. Employing a quantitative survey research design, data were collected through an online questionnaire involving 30 Special Education Integration Program (SEIP) teachers from various schools in Sarawak selected through convenience sampling. Data were analysed using descriptive statistics in SPSS, and the reliability of the instrument was assessed using Cronbach’s alpha coefficient. Findings highlight that, despite adequate general pedagogical preparedness, teachers remain less confident in their mathematics-specific instructional competencies. Therefore, the study concludes with a recommendation for more structured and targeted professional training in mathematics pedagogy. This research offers valuable insights to stakeholders aiming to enhance special education training programs, thereby improving instructional effectiveness for SEN students.